Light from the spirit world : The pilgrimage of Thomas Paine and others to the seventh circle in the spirit world - Paine, Thomas (Spirit), 1737-1809; Hammond, C. (Charles), 1805?-1859 (Salt Lake City, UT : Project Gutenberg, 2022)
"Light from the Spirit World" by C. Hammond is a spiritual narrative written in the mid-19th century. The work explores themes of life after death through the experiences of Thomas Paine and other notable figures as they navigate the afterlife in a realm filled with spirits and wisdom. The narrative delves into the nature of existence, the significance of belief, and the desire for enlightenment beyond the grave. The beginning of this work introduces readers to Thomas Paine, who, upon facing death, engages in profound conversations with spirits, reflecting on his life and beliefs. He experiences visions that reveal the connections between the physical and spiritual worlds, culminating in his passing and subsequent exploration of his new existence in the spirit realm. Through dialogues with his spirit companions, Paine grapples with themes of faith, truth, and the potential for transformation in both realms, setting the stage for a journey filled with learning and understanding that transcends mortal life. (This is an automatically generated summary.)
Release date is 2022-12-04
Emmanuel Ackerman, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Spirit writings; Paine, Thomas, 1737-1809 -- Spiritualistic interpretations